Advancing international criminal justice in southeast Asia through the regionalisation of international criminal law - Tan, Alvin Poh Heng (2014)
Only two Association of Southeast Asian Nations (ASEAN) countries have ratified the International Criminal Court (ICC) Statute, and this number is unlikely to change dramatically in the near future. This research thus considers how international criminal justice (ICrimJ) can be advanced through the regionalisation of international criminal law (ICL), whilst also serving the interests of ASEAN Member States. The theoretical appeal, practical viability, and political acceptability of regional ICrimJ mechanisms are accordingly examined. Given that the establishment of the ICC has challenged the absolute sovereignty of States over the prosecution of international crimes, regional initiatives have added political allure as they not only better reflect local legal norms and political considerations, but also place the selection of ‘regional crimes’ and enforcement measures primarily in the hands of regional countries. In recognition of the 'ASEAN way' of making decisions, regional initiatives to further ICrimJ in Southeast Asia should be implemented gradually and driven internally through consultation and consensus. Moreover, to achieve the overarching ASEAN goal of maintaining regional peace and security, the modalities and practical effects of ICrimJ may require greater emphasis on deterrence and reconciliation, instead of punishment.